Feasibility and Safety of Mark-Guided Submucosal Tunneling Endoscopic Resection for Treatment of Esophageal Submucosal Tumors Originating from the Muscularis Propria: A Single-Center Retrospective Study. (1st July 2021) - Wu, Ben-hua; Shi, Rui-yue; Zhang, Hai-yang; Liu, Ting-ting; Tian, Yan-hui; Xiong, Feng; Xu, Zheng-lei; Zhang, Ding-guo; Li, De-feng; Yao, Jun; Wang, Li-sheng
Abstract : Background . Submucosal tunneling endoscopic resection (STER) has effectively removed esophageal submucosal tumors (SMTs) originating from the muscularis propria (MP) layer. However, clinical failure and adverse events of STER remain concerned. In this study, we described a mark-guided STER (markings before creating entry point) and evaluated its feasibility and safety for esophageal SMTs originating from MP. Methods . Patients receiving the mark-guided STER from October 2017 to July 2020 were included and followed up (ranged from 3 to 30 months). The primary outcomes included complete resection, en bloc resection, and R0 resection rates. The secondary outcomes included procedure duration, main complication, and residual lesions. Results . A total of 242 patients with 242 SMTs (median diameter of 22 mm, ranging from 7 mm to 40 mm) received the mark-guided STER. The median procedure duration was 55 min (ranging from 35 min to 115 min). The complete resection, en bloc resection, and R0 resection rates were 100%, 98.3%, and 97.5%, respectively. The adverse event rate was 4.5%. However, there was no severe complication. No residual SMTs were detected during the follow-up period. Logistic regression demonstrated that the SMT size and procedure duration were independent factors associated with en bloc resection (P = 0.02 and P = 0.04, respectively). Moreover, logistic regression demonstrated that the SMT size was an independent risk factor for main complications (P = 0.02 ). Conclusion . Mark-guided STER was feasible and safe to remove esophageal SMTs ≦40 mm. However, it is necessary to further verify the feasibility and safety for the esophageal SMTs >40 mm.